The Levellers : radical political thought in the English Revolution - Foxley, Rachel (Politics, culture, and society in early modern Britain., 2013)
The Leveller movement of the 1640s campaigned for religious toleration and a radical remaking of politics in post-civil war England. This book, the first full-length study of the Levellers for fifty years, offers a fresh analysis of the originality and character of Leveller thought. Challenging received ideas about the Levellers as social contract theorists and Leveller thought as a mere radicalisation of parliamentarian thought, Foxley shows that the Levellers' originality lay in their subtle and unexpected combination of different strands within parliamentarianism. The book takes full account of recent scholarship, and contributes to historical debates on the development of radical and republican politics in the civil war period, the nature of tolerationist thought, the significance of the Leveller movement and the extent of the Levellers' influence in the ranks of the New Model Army -- Publisher's website.